A methods engineering study on Vibelle Manufacturing Corporation - Reyes, Cheryl; Salazar, Kris.; Silvestre, Anais (Diliman, Quezon City College of Engineering, 2005)
Vibelle Manufacturing Corporation manufactures hair care and skin care products, cosmetics, and personal care products. The subject of the study is the company's Jergens lotion production line. Specifically, the group is focused on the Pre-assembly, Filling and Labeling areas, which are the most viable areas for study and revision. To document the company's present system, the group conducted interviews with the company's top management, as well as with many of the workers. Furthermore, the group gathered quantitative and qualitative data through direct observation of the facilities. The group also consulted regularly with the managers in order to be kept updated with the activities in the plant. The root causes of the problems found in the production line are (1) the unavailability of the workers in designated areas, (2) the unbalanced supply of materials, and (3) the constant build-up of products. All of these prevent the smooth flow of production, and cause (a) the unsightly clutter in specific production areas and (b) machine idle times. After establishing the causal relationship of these problems recommendations are made in order to help solve these dilemmas. For the Pre-Assembly area, a new floor plan layout was recommended to facilitate the easy flow of work and materials, and to provide more ergonomic working conditions. For the Filling Area, further utilization of the baskets found at the end of the conveyor belt, as containers for the filled bottles, are recommended. These will aid the easy transportation of the filled bottles from the Filling Area to the Labeling Area and will lessen the delays in the filling process that were caused by the unavailability of packaging materials and the packing and repacking of the filled bottles. Lastly, for the Labeling Area, it is recommended that the room adjacent to the Labeling Area, the idle Quarantine Area, be used for the packing process of the filled and labeled bottles. This will lessen the number of workers who crowd the Labeling Area and allow the workers to focus more on their designated work. Finally, a schedule was prepared by the group to aid the company in the implementation of the final recommendations.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Vibelle Manufacturing Corporation; Cosmetics industry; Systems analysis